The concept of happiness according to Ibn Hazm and Martin Seligman - Umam, Yaul; Noor, Rifqi Nazahah; Soleh, Achmad Khudori (Psikoislamika: Jurnal Psikologi Islam, 2025)
The purpose of this article is to describe the happiness of Ibn Hazm and Martin Seligman. Ibn Hazm was a Muslim philosopher, while Seligman was a modern psychologist and secularist. These different concepts of happiness are interesting to study because they represent two major paradigms: Islamic ethical spiritualism and modern positive psychology, which are rarely directly compared. This comparison offers novelty by opening up a more holistic perspective on happiness. The method used is qualitative research with a comparative approach and narrative review. The primary sources used are " Risala h fi Mudawah an-Nufus wa Tadzhib al-Akhlaq "by Ibnu Hazm and the book "Authentic Happiness" by Martin Seligman. The results show that: (1) Happiness according to Ibn Hazm can only be achieved through worship and getting closer to God. (2) Meanwhile, Seligman believes that complete happiness is the result of a combination of a pleasant life, a good life and a meaningful life. (3) Seligman's conception of happiness only focuses on world orientation. (4) On the other hand, both agree that maximizing positive potential is an important point in the route to achieving happiness. However, Ibn Hazm emphasized that awareness of weaknesses also needs to be done so that humans are free from the nature of 'ujub (arrogance). Keywords: Happiness; Ibn Hazm; Seligman